Kīpuka Kuleana: restoring relationships to place and strengthening climate adaptation through a community-based land trust - Barger, Sarah; Vaughan, Mehana Blaich; Aiu, Christina; Akutagawa, Malia K. H.; Beall, Elif C.; Luck, Jennifer; Cordy, Dominique; Maldonado, Julie (Frontiers in Sustainability, 2024)
This community case study explores how Kīpuka Kuleana, a Native Hawaiian women-led community-based land trust, revitalizes relationships between people and ʻāina (lands and waters) to perpetuate cultural practices that build climate resilience in Kauaʻi, Hawaiʻi. We demonstrate that ancestral land protection is foundational to climate change mitigation and adaptation efforts on Kauaʻi, an isolated rural island in the Pacific Ocean increasingly vulnerable to flooding and landslides, sea level rise, and other climate-related impacts. Kīpuka Kuleana strives to keep kupa ʻāina ʻohana (long-time families) -the anchors of community who care for, teach from, and maintain balance in their fragile environments -rooted to their homes amidst increasing gentrification, land dispossession, and climate-related disasters. Through our interwoven programs, we return lands to communities and communities to lands, a reciprocal process known as ʻāina hoʻi, to restore access to ʻāina for collective caretaking, place-based education, and spiritual rejuvenation. Our land trust partners with Indigenous and allied groups in Hawaiʻi, Louisiana, California and Borikén (Puerto Rico) to share learnings tied to land protection, disaster resilience, adaptation, and rematriation, or the restoration of relationships between Indigenous people and ancestral lands. We offer some of those lessons to illustrate how Indigenous-led community-based land trusts and stewardship efforts forge new possibilities for adapting in place and cultivating more connected, resilient ecosystems stewarded under Indigenous leadership, in alignment with the "Land Back" movement.